Impact of design factors on user satisfaction - Kwon, Minyoung (A+BE | Architecture and the Built Environment, 2020)
Personal control was one of the influential parameters for user satisfaction presented in chapter 5. Personal control is not related to architectural office design, and in this thesis it is not associated with privacy and communication with colleagues. Thermal and visual comfort is analysed exhaustively in this chapter. Psychological comfort is an extra parameter for user satisfaction studies since the design factors such as office layout could be correlated to privacy, communication and so on. As a next step, chapter 6 investigates influential office design factors on user satisfaction related to thermal, visual, and psychological comfort and predicting which design factors may bring better satisfaction to users. Section 6.2 presents design factors affecting user satisfaction based on literature review. Five office cases in the Netherlands with 579 office occupants were studied using questionnaires, and interviews with facility managers and architects (section 6.3). Different statistical analysis tests were conducted to summarise satisfaction factors (section 6.4). The relative importance of design factors is described in section 6.5, and a regression analysis was used to predict profound outcomes in section 6.6.